Programas esportivos no estado militar: ações do esporte para todos para a educação popular (1973-1990) - Teixeira, Sérgio (2015)
The purpose of this dissertation is to discuss the project Esporte para Todos (EPT) in Brasil, within the period between 1973 and 1990. The theme was selected due to the existence of propositions which exalted EPT as a democratic movement, inspired in the population, with spontaneity and in the spirit of improvisation, despite its apogee during the Brazilian military government. On the contrary, our hypothesis is that the EPT was devised with the aim of promoting social control, especially when the weakening military regime started adopting discourses to encourage popular participation in several spheres. Our objective is to present context configurations in which EPT movement was developed, that is, we intend to outline the articulations concerning political, economic, social, and educational dimensions established during the military regime, more precisely, from the beginning to the end of EPT. That entails going through national and international nuances in the second half of the 20th century which influenced in the deflagration of the military coup d\'etat in Brasil, in 1964. The documental scope comprises EPT documents, legislation related to the period handled, and interviews with people who took important roles in the conduct of EPT. With such documentation, it was possible to verify that EPT composed discussions demarcated in international scenery, concerning disputes between mass sports and high performance sports. The project was implemented in Brasil as a campaign in 1977, by means of proposals referring to mass sports dissemination which had been discussed since 1973. However, at the end of 1978, EPT campaign was officially discontinued. That could be attributed to the discomforts caused by the gathering of crowds at events, but the fact such events drew power disputes among characters in government ranks and even in the segments of Physical Education should not be neglected. From that point on, according to authors who took part of EPT, the project became an autonomous movement, free from state meddling and riddled with contributions of pluralism and decentralization. This study investigates the degree of hegemony conferred by EPT on the population in the fruition of informal physical activities. It is concluded here that EPT anchored on the endorsement of the State, resorting to popular repertory of informal physical activities in order to define itself as a movement permeated by the interests of the community. Nevertheless, this dissertation verifies that EPT did not reach enough cultural rooting to be considered a movement with popular matrix, unlike the informal sports activities historically present in the heart of communities. The institutionalization of EPT showed signs of weakness in the throes of military regime. At that point, the movement sponsored by the State started to give way to corporate interests in Physical Education market. This can be demonstrated by the poor legacy left by EPT.